Ice - Durst, Sarah Beth. (New York : Margaret K. McElderry Books, 2009)
A modern-day retelling of "East o' the Sun, West o' the Moon" in which eighteen-year-old Cassie learns that her grandmother's fairy tale is true when a Polar Bear King comes to claim her for his bride and she must decide whether to go with him and save her long-lost mother, or continue helping her father with his research.
Keywords: Fairy tales; Polar bear -- Fiction; Supernatural -- Fiction; Scientists -- Fiction; Arctic regions -- Fiction